Kansas Steer Futurities - The Record on Retained Ownership 1974-19831 - Lambert, C.; Simms, D.; Schalles, B.; Corah, L.; Kuhl, Gerry L.; Sands, M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Spring born steer calves, weaned and delivered to custom feedlots by Kansas producers, were fed to slaughter weight. Gain and carcass information was gathered on over 5,000 head fed in 53 separate tests since the fall of 1974. Retaining ownership of steers through the feedlot phase has been profitable for producers in six of the last nine years, and in only two years have losses been large. Those same calves, if sold at weaning, would have been profitable in only three of the last nine years, using Kansas Farm Management Association average costs of production. The cattle averaged 59 percent USDA Choice and 98.3 percent USDA Yield Grade 3 or trimmer carcasses. Death loss averaged 1.2 percent over the nine years. Breed groups with the ability to gain rapidly and grade USDA Choice were most profitable. There was an $86.63 difference in profit and a .7 lb per day difference in gain from the low to high gaining breed groups. Profit increased as yearling hip height and rib eye area increased while carcass quality grade and fat thickness decreased. Profitability leveled out when yearling hip height exceeded 47 inches, rib eye area exceeded 13.5 sq. in. and quality grade went below 50 percent Choice.
Keywords: Beef; Steer; Feedlot; Profit; Gain; Carcass weight